2017
DOI: 10.1021/acs.jafc.7b04044
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Mulberry (Morus alba L.) Extract against Benzo[a]pyrene Induced Skin Damage through Inhibition of Aryl Hydrocarbon Receptor Signaling

Abstract: Benzo[a]pyrene (B[a]P), a type of polycyclic aromatic hydrocarbon, is present in the atmosphere surrounding our environment. Although B[a]P is a procarcinogen, enzymatically metabolized benzo[a]pyrene-7,8-dihydrodiol-9,10-epoxide (BPDE) could intercalate into DNA to form bulky BPDE-DNA adducts as an ultimate carcinogenic product in human keratinocytes. The aim of this study was to evaluate the protective effect of mulberry extract, purified from the fruit of Morus Alba L., on B[a]P-induced cytotoxicity in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…cyp1a1 and cyp1b1 mRNA were upregulated nearly 1.5‐fold under coexposure to B[a]P and FICZ when compared to B[a]P alone. B[a]P‐mediated apoptosis affects the transcription of mitochondrial apoptosis‐related proteins (Bcl2 and Bax) and P53 activation (Banerjee, Chakraborty et al, 2016; Woo al., 2017). In this study, B[a]P exposure significantly downregulated the mRNA levels of the antiapoptotic gene Bcl2 ( p < .01) and upregulated the expression of P53 ( p < .01) compared to the control group (Figure 5c,d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…cyp1a1 and cyp1b1 mRNA were upregulated nearly 1.5‐fold under coexposure to B[a]P and FICZ when compared to B[a]P alone. B[a]P‐mediated apoptosis affects the transcription of mitochondrial apoptosis‐related proteins (Bcl2 and Bax) and P53 activation (Banerjee, Chakraborty et al, 2016; Woo al., 2017). In this study, B[a]P exposure significantly downregulated the mRNA levels of the antiapoptotic gene Bcl2 ( p < .01) and upregulated the expression of P53 ( p < .01) compared to the control group (Figure 5c,d).…”
Section: Resultsmentioning
confidence: 99%
“…Long‐term and low‐dose exposure of mice to B[a]P induces hepatocellular carcinoma metastasis and progression (Ba et al, 2015). Exogenous pollutants (polychlorinated biphenyls), antioxidants (polyphenols), and plant extracts (flavonoids) have been reported to reduce the toxic effects of B[a]P (Al‐Anati, Högberg, & Stenius, 2010; P. Nair et al, 2015; Woo et al, 2017). Previous studies have shown that in breast cancer cells, the endogenous AhR ligand, kynurenine, a product produced by tryptophan, inhibited the TCDD‐induced apoptotic response (Bekki, Vogel, Li, Ito, & Sweeney, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Q at 1 μM exhibited a modest capacity to decrease TNF-α effect on fibroblastś cell cycle by reducing about 10% the number of cells in phase S. Although this effect was rather moderate, it has to be considered that the continuous exposure of intestinal cells to Q due to the repeated consumption of BW products could help prevent/regulate cell cycle alteration during intestinal inflammation. A possible mechanism by which BW products could regulate the TNF-α-altered cell cycle checkpoint function is the modulation of cyclins 61, 62 as well as AhR 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that, in addition to its Nrf2 effects, the co-treatment of Urban Dust and S.C. improved the anti-oxidant gene expression ( Figure 4) and induced a significant decrease in AhR expression ( Figure 5), as compared to Urban Dust alone. Recently, Woo et al also noted that cyanidin-3-glucoside (C3G), a major active compound of mulberry extract, showed biological activities that protect the cells from pollutants, which can be attributed to the AhR signaling pathway being repressed [37]. Various compounds, such as plant polyphenols (e.g., resveratrol and curcumin) also directly or indirectly activate AhR, while other compounds are thought to be AhR antagonists [38,39].…”
Section: Discussionmentioning
confidence: 99%